ANALISIS PENGARUH SUKU BUNGA, INFLASI, NILAI TUKAR DAN HARGA MINYAK DUNIA TERHADAP JAKARTA ISLAMIC INDEX (PERIODE 2009 -2013) - B11111048, Dewi Permatasari (Jurnal Manajemen Update, 2015)
Capital market is one of the macro-economic indicators, which is very important for a country. One way to measure of stock market performance is a stock index. This study uses the Jakarta Islamic Index as a benchmark for the Composite Stock Price Index. Stock index itself is influenced by several factors consist of internal factors and external factors. But in this study only tested the influence of some external factors (macro economic) consisting of BI interest rates, inflation, exchange rates and world oil prices to return JII index during the observation period January 2009 - December 2013. Data analysis method used is multiple linear regression analyzes were performed with SPSS version 16. The result showed that partially BI rate and inflation has a negative and not significant influence, the exchange rate has a positive and not significant effect while world oil prices have and a significant negative influence on the index returnÂ  Jakarta Islamic Index and together all the research variables affect the Jakarta Islamic Index return. Additionally obtained adjusted R-square value is 0.112 indicates that the variation of the independent variables are able to explain 11.2% variation of the dependent variable, while the remainder is equal to 88.8% is explained by other variables outside independent variables, which means that the ability of the independent variable dependent variable explained very limited. Keywords : Capital Market, Macro-economic, BI Interest rate, Inflation, Exchange Rate, World Oil Prices, Return JII Index.